PENERAPAN MODEL PICTURE WORD INDUCTIVE DALAM PEMBELAJARAN MENULIS TEKS PERSUASI BERDASARKAN STRUKTUR DAN KAIDAH KEBAHASAAN PADA PESERTA DIDIK KELAS VIII SMPN 1 NAGREG TAHUN PELAJARAN 2022/2023 - Fitriana Indah Sari; Titin Nurhayatin; Musaddad Abdul Azis (STKIP Subang, 2023)
The low ability of students to write persuasive texts is the background for this research. The lack of use of innovative learning models by educators is one of the causes of this. It is known that incorporating the model into the learning process helps to increase the motivation and interest of students. The purpose of this research is to improve students' ability to write persuasive texts according to the structure and rules of the language. In addition, this study also aims to describe the differences in students' ability to write persuasive texts between the experimental class using the inductive picture word model and the control class using the question and answer learning model and to test the effectiveness of the inductive picture word model in learning to write persuasive texts. The method used in this research is a quasi-experimental method with nonequivalent control group design. Data collection techniques using literature study techniques, trials, observations and tests. The data collected were the results of the pretest and posttest from the experimental class and the control class of class VIII students of SMPN 1 Nagreg. The results obtained based on the Wilcoxon test are the Asymp values. Sig. (2-tailed) shows 0.000 <0.05 meaning that the hypothesis that there is a difference in the ability to write persuasive texts between the experimental class using the inductive picture word model and the control class using question and answer learning is acceptable. The results of the mann whitney test are Asymp. Sig. (2-tailed) shows 0.000 <0.05 meaning that the hypothesis that the inductive picture word model is effectively used in learning to write persuasive texts is acceptable.